Resilient cities : overcoming fossil fuel dependence - Newman, Peter, 1945-; Beatley, Timothy, 1957-; Boyer, Heather (Island Press/Center for Resource Economics : Imprint : Island Press, 2017)
What does it mean to be a resilient city in the age of a changing climate and growing inequity? As urban populations grow, how do we create efficient transportation systems, access to healthy green space, and lower-carbon buildings for all citizens? Peter Newman, Timothy Beatley, and Heather Boyer respond to these questions in the revised and updated edition of Resilient Cities. Since the first edition was published in 2009, interest in resilience has surged, in part due to increasingly frequent and deadly natural disasters, and in part due to the contribution of our cities to climate change. The number of new initiatives and approaches from citizens and all levels of government show the promise as well as the challenges of creating cities that are truly resilient. Resilient Cities, Second Edition reveals how the resilient city characteristics have been achieved in communities around the globe. The authors offer stories, insights, and inspiration for urban planners, policymakers, and professionals interested in creating more sustainable, equitable, and, eventually, regenerative cities. Most importantly, the book is about overcoming fear and generating hope in our cities. Cities will need to claim a different future that helps us regenerate the whole planet-this is the challenge of resilient cities.- Resumé vydavatel
Keywords: životní prostředí měst; urbanismus; udržitelný rozvoj; doprava; urban ecology; city planning; sustainable development; transportation; elektronické knihy; monografie; electronic books; monographs